ECONOMIC AND SOCIAL PROCESSES IN THE UZBEK SSR DURING WORLD WAR II (World Conference on Social Sciences, Law and Public Policy, 2026)
This article exaines the economic and social processes in the Uzbek SSR during World War II. The study analyzes industrial production, agricultural output, labor mobilization, demographic changes, and social adaptation resulting from wartime policies. Archival documents and statistical data reveal the republic’s contributions to the Soviet war effort, including resource allocation, workforce participation, and social resilience. Findings provide insights into the adaptation of regional economies and societies under extreme wartime pressures.
Keywords: World War II, Uzbek SSR, economic development, social changes, industrial production, agriculture, labor mobilization, wartime economy, demographic shifts, Soviet Union.